Instructional Innovation in STEM: Using the ASSURE Model for Video-based programming instruction in Engineering - Llewellyn Liu; Dorothy DeWitt (Research Synergy Foundation, 2025)
The increasing demand for programming skills among engineering students has highlighted the need for more engaging and effective instructional methods. This study explores the application of the ASSURE instructional design model in developing video-based programming instruction tailored specifically for undergraduate engineering students. By aligning technological tools with pedagogical strategies, the ASSURE model provides a structured yet flexible framework for integrating multimedia into STEM education. The study outlines the design process, implementation, and evaluation of a video-based module for teaching VHDL (VHSIC Hardware Description Language) programming. Using the USE Usability Framework, the pilot implementation findings indicate positive feedback on the learning experience. The study concludes with practical implications for engineering educators and recommendations for future instructional design in technology-enhanced STEM education.